Exploring postgraduate students’ experience with rubric-referenced assessment: limitations and solutions - Liang, Jing Teh; Su, Luan Wong; Md Khambari, Mas Nida; O. K. Rahmat, Rahmita Wirza; Sai, Hong Tang (Universiti Putra Malaysia, 2025)
Despite the various benefits of rubric-referenced assessment (RRA), multiple studies have revealed its potential pitfalls. Given the scarcity of research on the limitations of RRA and its solutions in the context of Malaysian postgraduates, this study explores the limitations of RRA and proposes potential strategies for improvement from the perspective of postgraduate students in Malaysia. The study adopted a case study qualitative approach and the Activity Theory as the theoretical framework. Five Malaysian postgraduate students provided their responses via two focus group discussions. The participants highlighted that rubrics may stifle creative self-expression, cause inconsistency in scoring, cause confusion among students, and be limited in catering to various learner needs. To address these issues, the participants recommended that the instructor allocate time for students to understand the rubric and engage in discussion about its content. They also proposed flexibility in rubrics to accommodate revisions based on student feedback and implementing scoring calibration sessions or training to maintain scoring consistency. Other suggestions comprised prioritising inclusive assessments, tailoring rubrics for different learner profiles, including specific numerical indicators in rubric descriptions, using a holistic rubric, and providing feedback to students according to the rubric.